2023
DOI: 10.1093/bioinformatics/btad005
|View full text |Cite
|
Sign up to set email alerts
|

A multi-view latent variable model reveals cellular heterogeneity in complex tissues for paired multimodal single-cell data

Abstract: Motivation Single-cell multimodal assays allow us to simultaneously measure two different molecular features of the same cell, enabling new insights into cellular heterogeneity, cell development, and diseases. However, most existing methods suffer from inaccurate dimensionality reduction for the joint-modality data, hindering their discovery of novel or rare cell subpopulations. Results Here, we present VIMCCA, a computationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Most of the works used CNN as the DL method for classifying metagenomic samples. There are few works which used GCN and variational auto encoders (VAE) for feature extraction and reduction from genomic data [ 22 – 25 ]. However, to the best of our knowledge, we observed that GNNs, such as GraphSAGE, have not been widely applied in the area of microbiome analysis to predict diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the works used CNN as the DL method for classifying metagenomic samples. There are few works which used GCN and variational auto encoders (VAE) for feature extraction and reduction from genomic data [ 22 – 25 ]. However, to the best of our knowledge, we observed that GNNs, such as GraphSAGE, have not been widely applied in the area of microbiome analysis to predict diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Single-cell multi-view data has emerged in recent years, driven by advancements in sequencing technology that enable researchers to collect information from various views of the same cell [35]. The integration of data from multiple views provides a comprehensive understanding of cell characterization.…”
Section: B Multi-view Clustering Methods For Single-cell Datamentioning
confidence: 99%
“…These techniques have demonstrated their effectiveness in various applications and experimental setups. Simultaneously, several algorithms have been put forth for paired data, which encompass Seurat v4 ( Hao et al 2021 ), totalVI ( Gayoso et al 2021 ), and VIMCCA ( Wang et al 2023 ), along with various others. It is important to note that while these methods excel in many scenarios, they are often customized to specific modalities or application contexts.…”
Section: Introductionmentioning
confidence: 99%